(untitled) (Fiep Bulletin - online, 2016)
Physical Education stands out in today’s environment through scientific research proving its importance for health preventing diseases linked to physical inactivity. The elaboration of didactic materials by government agencies as well as the creation of laws and opinions related to Brazilian education justified and include physical education as a compulsory subject to be imaged in schools. To understand the physical education as the health and relevant discipline in school levels should be aware of their transformations in society knowing your requirement and legitimacy. This article aims to analyze content found on the Ministry of Education website referring to the Brazilian education legislation with regard to the discipline of Physical Education in Basic Education and describe the function of the Federal Council of Physical Education (CONFEF) relating to the exercise of profession in Frederick / RS and region. Were taken into account, opinions and resolutions issued by the National Board of Education between the periods 1996-2013, as well as the Laws and Guidelines found in that site, CONFEF status and articles on public policy. According to the documentation examined, the role of CONFEF and the relationship with acting in the region, we observed a deficiency with regard to monitoring the performance of qualified professionals for the work to be carried out in public school environments and little collection by the managers with regard to the quality of the professionals work. Finally, we highlight the importance of people’s participation in discussions on matters which are decided by our leaders in seeking to meet the needs and peculiarities of the profession.